Connections between Certain Subclasses of Analytic Univalent Functions Based on Operators. (15th November 2017) - Ezhilarasi, R.; Sudharsan, T. V.; Haji Mohd, Maisarah; Subramanian, K. G.
Abstract : In this paper, by applying the Hohlov linear operator, connections between the class S D ( α ), α ≥ 0, and two subclasses of the class A of normalized analytic functions are established. Also an integral operator related to hypergeometric function is considered.